Estimation of sprint performances in the breaststroke from body characteristics - Daly, D.; Persyn, U.; van Tilborgh, L. (Swimming Science V, 1988)
In a previous study, equations for 100- and 400-m crawl performance estimations were developed from factor scores calculated from 18 anthropometric, 6 flexibility, and 5 strength measures and V02 intake (Daly, Tilborgh, & Persyn, 1984). The error in estimation was around 3% for varying distances and crawl patterns. In this study equations were developed for the 100-m breaststroke with the intention of making field diagnoses, using a personal computer. A smaller number of easy measures was selected, and the factor scores were no longer calculated. In addition, the time-consuming vo2 intake test was eliminated.